Clinicopathological Features of Remnant Gastric Cancer (RGC): Detection of RGC after Five Years of Follow-Up Was Associated with a Poor Prognosis. Issue 4 (April 2019) - Kameda, Chizu; Kawabata, Ryohei; Koga, Chikato; Matsumura, Tae; Murakami, Masahiro; Noura, Shingo; Shimizu, Junzo; Hasegawa, Junichi
The purpose of this study was to evaluate the clinicopathological features and prognosis of patients who underwent surgery for remnant gastric cancer (RGC) during/after the regular five-year follow-up period after initial distal gastrectomy for gastric cancer that is recommended by the Japanese gastric cancer treatment guidelines. Between January 2007 and December 2017, 40 patients underwent surgery for RGC after distal gastrectomy. Twenty-eight of the 40 patients underwent initial gastrectomy for cancer. We divided the 28 patients into two groups: patients who were diagnosed with RGC during/after the five-year follow-up period after initial gastrectomy, and analyzed their retrospectively collected data. Among the 28 patients, 15 patients were diagnosed with RGC within five years and 13 patients were diagnosed with RGC after five years. There were significant differences in the reconstruction of the initial operation, curative resection, pathological depth of the tumor, and pathological stage of the two groups. Multivariate analyses revealed that the interval between initial gastrectomy and RGC and the pathological TNM stage were significant risk factors for shorter cancer-specific survival. Kaplan-Meier analyses demonstrated that patients with RGC after the five-year follow-up period had a significantly worse prognosis in terms of cancer-specific survival than those who developed RGC within five years. This study suggested surveillance by using the annual endoscopy might be necessary beyond the initial five-year period for patients who underwent gastrectomy for gastric cancer.